[tex]\frac{x+32}{11}[/tex] + [tex]\frac{x+32}{12}[/tex] = [tex]\frac{x+38}{13}[/tex] + [tex]\frac{x+27}{14}[/tex].
Mình nghĩ là bạn sai đề đấy. Mình nghĩ đề là thế này:
[tex]\frac{x+30}{11}[/tex] + [tex]\frac{x+29}{12}[/tex] = [tex]\frac{x+28}{13}[/tex] + [tex]\frac{x+27}{14}[/tex].
<=> ([tex]\frac{x+30}{11}[/tex] + 1) + ([tex]\frac{x+29}{12}[/tex] + 1) = ([tex]\frac{x+28}{13}[/tex] + 1) + ([tex]\frac{x+27}{14}[/tex] + 1).
<=> [tex]\frac{x+41}{11}[/tex] + [tex]\frac{x+41}{12}[/tex] = [tex]\frac{x+41}{13}[/tex] + [tex]\frac{x+41}{14}[/tex].
<=> [tex]\frac{x+41}{11}[/tex] + [tex]\frac{x+41}{12}[/tex] - [tex]\frac{x+41}{13}[/tex] - [tex]\frac{x+41}{14}[/tex] = 0.
<=> (x+41)([tex]\frac{1}{11}[/tex] + [tex]\frac{1}{12}[/tex] - [tex]\frac{1}{13}[/tex] - [tex]\frac{1}{14}[/tex]) = 0.
Ta thấy [tex]\frac{1}{11}[/tex] + [tex]\frac{1}{12}[/tex] - [tex]\frac{1}{13}[/tex] - [tex]\frac{1}{14}[/tex]) luôn khác 0.
=> x + 41 = 0.
=> x = -41.